2000
DOI: 10.1038/sj.leu.2401873
|View full text |Cite
|
Sign up to set email alerts
|

Oral 9-cis retinoic acid (Alitretinoin) in the treatment of myelodysplastic syndromes: results from a pilot study

Abstract: A multicenter phase II study was initiated to investigate the efficacy, toxicity and tolerability of an oral regimen of 9-cis retinoic acid (9CRA) as a differentiation-inducing agent stimulating both retinoic acid receptor (RAR) and retinoic X receptor (RXR). Thirty patients with myelodysplastic syndromes (MDS) were enrolled into the study. The MDS subtypes were distributed as follows: 14 refractory anaemia (RA), four refractory anaemia with ringed sideroblasts (RARS), and 12 refractory anaemia with excess bla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…However, in human clinical trials, 9-cis RA has been found to have significant toxicity (34). Therefore, receptor-selective retinoids that have reduced toxicity are now being developed as potential chemopreventive agents.…”
Section: Discussionmentioning
confidence: 99%
“…However, in human clinical trials, 9-cis RA has been found to have significant toxicity (34). Therefore, receptor-selective retinoids that have reduced toxicity are now being developed as potential chemopreventive agents.…”
Section: Discussionmentioning
confidence: 99%
“…alitretinoin, panobinostat, and progesterone. Both alitretinoin, a geometric isomer of tretinoin currently used in the treatment of Acute Promyelocytic Leukemia (a subclass of AML) [34] , and panobinostat, a histone deacetylase inhibitor commonly used in multiple myeloma [35] , have been investigated for use in AML [36][37][38][39] . Lastly, while progesterone itself has not, to our knowledge, been suggested for AML treatment, a synthetic progestin, medroxyprogesterone acetate, has recently been suggested as a possible drug repositioning candidate for AML [40] .…”
Section: Epigenome-based Repositioning Using Publicly Available Aml Dmentioning
confidence: 99%
“…51 9-cis retinoic acid, a ligand for both the RAR and RXR receptors, has shown activity in MDS. 22 ATRA has proven effective in other diseases, notably in acute promyelocytic leukemia, inducing differentiation and remissions which are karyotypically normal. 52 Clinical trials investigating the effects of PB on patients with acute myeloid leukemia and myelodysplasia have yielded promising changes in hematopoietic parameters including increased platelets and neutrophils, as well as decreased blasts.…”
Section: Figurementioning
confidence: 99%
“…16 We have recently shown that the biological activities of PB are closer to that of BA than PA. 53 Early studies of 13-cis retinoic acid, 9-cis retinoic acid, and all-trans retinoic acid (ATRA) have suggested limited clinical activity of these agents in MDS. [17][18][19][20][21][22] The present studies were undertaken to investigate whether the addition of retinoic acid could improve the pharmacodynamic profile of PB on the ML-1 myeloid leukemia cell model. Our studies show that ATRA acts synergistically with PB to induce differentiation and cell cycle arrest.…”
Section: Introductionmentioning
confidence: 99%